Technique and Results of Direct Measurement of Intracranif Pressure - Palma, Eduardo C; Rodríguez Martínez, Ricardo; Garbino, Carlos (Cirugía del Uruguay, 1980)
Out of 593 cases of intracranial puncture of cisterna magna, -529 were positive; in 64, puncture was negative due to cisterna! blockade with no disorders. Direct measurement of intracranial pressure in the cisterna magna was performed under local anesthesia with patient seated.